THE CONCEPT OF CRIMINAL LAW PROVISION OF OPERATIONAL-SEARCH ACTIVITIES AND A BRIEF DESCRIPTION OF ITS DIRECTIONS - Barseghyan, Gevorg (State and Law, 2025)
The aim of this article is to explore the concept and briefly characterize the directions of criminal-legal provision for operational-search activities. Studying operational-search activities solely from an investigative or criminal procedural perspective is insufficient, as several issues related to these activities require regulation under criminal law. These issues include, in particular, the criminal-legal response to cases where individuals conducting operational-search activities cause harm to legally protected interests, the problem of entrapment during operational-search measures, criminal liability of the provocateur and the individual who committed a crime as a result of provocation, as well as the legal modeling (refinement and/or development) of criminal offenses aimed at ensuring the effectiveness of operational-search activities. Based on the results of the conducted research, the Article develops the concept of criminal-legal provision of operational-search activities. Criminal-legal provision of operational-search activities is the process and outcome of legal regulation aimed at ensuring the effectiveness of operational-search activities and safeguarding them from internal and external destabilizing interference. It also encompasses the application of criminal-legal norms regulating the public relations that arise during the activities of individuals conducting operational-search activities within the scope of their powers. From the proposed definition, it follows that criminal-legal provision of operational-search activities has both regulatory and protective directions, in accordance with the issues, methods, and means of criminal legislation. These directions are interconnected and complementary mechanisms. The first direction—regulatory—should primarily be expressed through the development of a norm that excludes criminal liability in cases where individuals conducting operational-search activities lawfully cause harm to legally protected interests. The second direction—protective—should manifest itself in the refinement or development of the criminal structures in the Special Part of the Criminal Code.